Making co-enrolment feasible for randomised controlled trials in paediatric intensive care. - Katie Harron; Twin Lee; Tracy Ball; Quen Mok; Carrol Gamble; Duncan Macrae; Ruth Gilbert; CATCH team (PLoS ONE)
Aims Enrolling children into several trials could increase recruitment and lead to quicker delivery of optimal care in paediatric intensive care units (PICU). We evaluated decisions taken by clinicians and parents in PICU on co-enrolment for two large pragmatic trials: the CATCH trial (CATheters in CHildren) comparing impregnated with standard central venous catheters (CVCs) for reducing bloodstream infection in PICU and the CHIP trial comparing tight versus standard control of hyperglycaemia. Methods We recorded the period of trial overlap for all PICUs taking part in both CATCH and CHiP and reasons why clinicians decided to co-enrol children or not into both studies. We examined parental decisions on co-enrolment by measuring recruitment rates and reasons for declining consent. Results Five PICUs recruited for CATCH and CHiP during the same period (an additional four opened CATCH after having closed CHiP). Of these five, three declined co-enrolment (one of which delayed recruiting elective patients for CATCH whilst CHiP was running), due to concerns about jeopardising CHiP recruitment, asking too much of parents, overwhelming amounts of information to explain to parents for two trials and a policy against co-enrolment. Two units co-enrolled in order to maximise recruitment to both trials. At the first unit, 35 parents were approached for both trials. 17/35 consented to both; 13/35 consented to one trial only; 5/35 declined both. Consent rates during co-enrolment were 29/35 (82%) and 18/35 (51%) for CATCH and CHiP respectively compared with 78% and 51% respectively for those approached for a single trial within this PICU. The second unit did not record data on approaches or refusals, but successfully co-enrolled one child. Conclusions Co-enrolment did not appear to jeopardise recruitment or overwhelm parents. Strategies for seeking consent for multiple trials need to be developed and should include how to combine information for parents and patients.